Incomplete Bessel Polynomials: A New Class of Special Polynomials for Electromagnetics; Progress In Electromagnetics Research M; Vol. 84 - Li Lin; Antipov P. A. Pyotr Aleksandrovich; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Gubarev F. A. Fedor Aleksandrovich (2019, 2019)
Title screen